2000
DOI: 10.1021/jm9909490
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Polycyclic Acridines. 7. Synthesis and Biological Properties of DNA Affinic Tetra- and Pentacyclic Acridines

Abstract: New synthetic routes to a series of tetra- and pentacyclic acridines related in structure to marine natural products are reported. The novel water-soluble agent dihydroindolizino[7,6,5-kl]acridinium chloride 14 has inhibitory activity in a panel of non-small-cell lung and breast tumor cell lines exceeding that of m-AMSA. The salt inhibited the release of minicircle products of kDNA confirming that disorganization of topoisomerase II partly underlies the activity of the compound. COMPARE analysis of the NCI mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 26 publications
(81 reference statements)
1
52
0
Order By: Relevance
“…One of the lead compounds, dihydroindolizino[7,6,5-kl]-acridinium chloride (DS, Fig. 1) displayed growth inhibitory activity at sub-micromolar concentration range in panels of breast and non-small cell lung cancer cell lines [20]. The compound formed a binding ‘hot spot’ in DNA with the planar pyridoacridine moiety intercalating at G–C sequences and the pyrrolidinium fragment occupying minor or major grooves [21].…”
Section: The Cover Image Contestmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the lead compounds, dihydroindolizino[7,6,5-kl]-acridinium chloride (DS, Fig. 1) displayed growth inhibitory activity at sub-micromolar concentration range in panels of breast and non-small cell lung cancer cell lines [20]. The compound formed a binding ‘hot spot’ in DNA with the planar pyridoacridine moiety intercalating at G–C sequences and the pyrrolidinium fragment occupying minor or major grooves [21].…”
Section: The Cover Image Contestmentioning
confidence: 99%
“…1), which is also an acridine derivative, DS was not susceptible to P -glycoprotein-mediated drug efflux and retained activity in lung and breast cancer cells made resistant to the topoisomerase II inhibitors (etoposide and doxorubicin) [20]. In addition, the compound was shown to be more potent than amsacrine and etoposide in breast cancer cells with varying molecular characteristics [20]. Assessment of mode of cell death induced by the compound revealed SKBr-3 breast cancer cells underwent apoptosis, as observed with the aid of scanning electron microscopy (Fig.…”
Section: The Cover Image Contestmentioning
confidence: 99%
“…In COMPARE analysis (NCI), compounds with a Pearson correlation coefficient greater than 0.6 often function though a biochemically related mechanism [157]. The pyridoacridine alkaloids were subjected to COMPARE analysis and showed a correlation pattern consistent with topo II inhibitors [158].…”
Section: Topoisomerasesmentioning
confidence: 99%
“…Many approaches by modifying acridine monomer (Antonini et al, 1995;Stanslas et al, 2000;Antonini et al, 2001;Charmantray et al, 2003) or dimer (Antonini et al, 2003;Wakelin et al, 2003;Wang et al, 2007) to increase cancer chemosensitivity have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%